Grass and subschrub layer as a structural component of forest communities in the North-East of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The main structural features of herbaceous and subshrub layer have been analyzed, and its functional role has been defined on the example of the forests of Ukrainian Polissya. High floristic biodiversity in forest ecosystems and heterogeneity of their flora have been specified on the basis of comparative floristic analysis. About 5–6 environmental groups are distinguished within each syntaxon in herbaceous and subshrub layer. Their number depends on the composition of forest stand, surface pattern and soil cover. Depending on the ecological-coenotic situation, all plant species of herbaceous and subshrub layer are distinct in going through the stages of ontogenesis, type of morphogenesis, life status, etc. Individual ecological amplitudes of forest herbs conform to environmental regimes of the relevant syntaxon, and with the proper management of these forests, the structure of the lower tiers will preserve its integrity and identity in the protected natural areas. The success of tree regeneration period is largely determined by the composition and structural features of ground vegetation.
Keywords: herbaceous and subshrub layer, forest phytocenoses, Ukrainian Polissya.